2014
DOI: 10.1371/journal.pone.0105991
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Suppressor MicroRNA-27a in Colorectal Carcinogenesis and Progression by Targeting SGPP1 and Smad2

Abstract: The aberrant expression of microRNAs (miRNAs) is associated with colorectal carcinogenesis, but the underlying mechanisms are not clear. This study showed that the miRNA-27a (miR-27a) was significantly reduced in colorectal cancer tissues and colorectal cancer cell lines, and that the reduced miR-27a was associated with distant metastasis and colorectal cancer clinical pathological stages–miR-27a was lower at stages III/IV than that at stage II. Bioinformatic and systemic biological analysis predicted several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 45 publications
1
92
0
Order By: Relevance
“…We selected the SMAD2 and SMAD4 genes as potential targets of miR‐27a in lung cancer. Recent studies have also reported that miR‐27a regulated SMAD2 and SMAD4 in human lung fibroblasts and SGPP1 and SMAD2 in human colorectal cancer . In addition, upregulation of miR‐27a has been reported in a number of cancers, such as breast cancer, gastric adenocarcinoma, pancreatic carcinoma, and lung cancer, describing it as an oncogene.…”
Section: Discussionmentioning
confidence: 93%
“…We selected the SMAD2 and SMAD4 genes as potential targets of miR‐27a in lung cancer. Recent studies have also reported that miR‐27a regulated SMAD2 and SMAD4 in human lung fibroblasts and SGPP1 and SMAD2 in human colorectal cancer . In addition, upregulation of miR‐27a has been reported in a number of cancers, such as breast cancer, gastric adenocarcinoma, pancreatic carcinoma, and lung cancer, describing it as an oncogene.…”
Section: Discussionmentioning
confidence: 93%
“…These oncomiRs effect CRC cell proliferation, apoptosis, migration and invasion (12). However, another type of miRNA, termed tumor suppressive miRs (tsmiRs), are significantly downregulated in human colorectal adenocarcinoma tissue samples compared with the adjacent normal colorectal tissues, including miR-339-5p, miR-27a and miR-139-5p (13)(14)(15). miR-517a is considered to be a novel oncomiR and was observed to be elevated in human hepatocellular carcinoma (HCC) (16); expression of miR-517a increased proliferation, migration, and invasion of HCC cells in vitro (16).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that miRNA might play critical roles in cancer initiation and the progression processes, including DLBCL . MiR‐27a, which located at chromosome 19, has been reported to be associated with several types of cancer, such as colon cancer, breast cancer, gastric adenocarcinoma, and pancreatic carcinoma . In addition, several studies have investigated the relationship between Pre‐miR‐27a rs895819 polymorphism and risk of cancer such as colorectal cancer, cervical cancer, and gastric cancer .…”
Section: Introductionmentioning
confidence: 99%